2021
DOI: 10.3389/fbioe.2021.695850
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1: A Promising Therapeutic Target for Peripheral Nerve Injury

Abstract: Patients who sustain peripheral nerve injuries (PNIs) are often left with debilitating sensory and motor loss. Presently, there is a lack of clinically available therapeutics that can be given as an adjunct to surgical repair to enhance the regenerative process. Insulin-like growth factor-1 (IGF-1) represents a promising therapeutic target to meet this need, given its well-described trophic and anti-apoptotic effects on neurons, Schwann cells (SCs), and myocytes. Here, we review the literature regarding the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…In this study, we identified IGF1 as a key endogenous signaling molecule secreted by human SFRP4 + stromal cells during the regenerative phase of the menstrual cycle, which regenerates endometrial epithelial organoid formation in vitro, gland formation in vivo and full-thickness endometrial regeneration. This identification provided a promising bioactive molecule for tissue engineering and regenerative medicine treatment of endometrial injury, thin endometria, and intrauterine adhesion, as IGF1 was reported to be functional in the treatment of injury in peripheral Nerve 31 and cartilage reconstruction in Osteoarthritis 32 . In addition to its role in the endometrial epithelia, IGF1 was also shown to promote interleukin 10 (IL10) expression in bone marrow stem cells, which suggests additional functions of IGF1 in immune regulation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified IGF1 as a key endogenous signaling molecule secreted by human SFRP4 + stromal cells during the regenerative phase of the menstrual cycle, which regenerates endometrial epithelial organoid formation in vitro, gland formation in vivo and full-thickness endometrial regeneration. This identification provided a promising bioactive molecule for tissue engineering and regenerative medicine treatment of endometrial injury, thin endometria, and intrauterine adhesion, as IGF1 was reported to be functional in the treatment of injury in peripheral Nerve 31 and cartilage reconstruction in Osteoarthritis 32 . In addition to its role in the endometrial epithelia, IGF1 was also shown to promote interleukin 10 (IL10) expression in bone marrow stem cells, which suggests additional functions of IGF1 in immune regulation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of Igf‐1, a growth hormone and associated with tissue regeneration and repair (Slavin et al, 2021), in CPZ‐fed C57Bl/6 mice coincides with the appearance of OPC, suggesting a protective role for Igf‐1 (Mason et al, 2000). While the source of Igf‐1 was not investigated in that study (Mason et al, 2000), another study revealed that the astrocytic expression of Igf‐1 was associated with remyelination (Schulz et al, 2012).…”
Section: Microglial Role In Myelination Following Cns Injurymentioning
confidence: 99%
“…Schwann cells play an irreplaceable role during NMJ regeneration since they could guide axons to achieve the original NMJs sites and remyelinate them ( Gordon, 2020 ; Nocera and Jacob, 2020 ). The GH-IGF-1 system has been proven to have the potential to improve outcomes after the nerve injury ( Tuffaha et al, 2016 ; Lopez et al, 2019 ; Slavin et al, 2021 ). Also, it has been demonstrated that during the regeneration period, GH and IGF-1 support SCs myelination and inhibit SCs apoptosis.…”
Section: Neuromuscular Junction Protection Strategies and Their Clini...mentioning
confidence: 99%